Evaluation and Assessment Environmental Sustainability (Case Study: Ardebil Province) - Hossain Nazmfar; sarideh Alavi; Ali EShghiChharborj; Gholamreza Ahmadzadeh (جغرافیا و پایداری محیط, 2018)
The development of discussions about industry and its effects on the environment, along with population growth, led to a sustainability paradigm in the world. Sustainability roots in environmental thoughts which is a multidimensional phenomenon nowadays including social, economic, and environmental issues. Therefore, this study aimed to evaluate and assess the sustainability of development in economic, social and environmental aspects in the counties of Ardabil Province. The research method is descriptive-analytical and quantitative. The population consists of 10 counties of Ardebil Province, based on census in 2015 and 2014. 3 economic, social and environmental components consisting of 10 economic indices, 16 social indices, and 14 environmental indices were used to evaluate. In this study, Analytic Network Process model (ANP) was used to express the relative importance of each indicator, and the sustainable barometer model was used to analyze the data. The results show that among the triple sustainability aspects, the economic aspect has more sustainability in comparison to the social and environmentally aspects. Indices of economic and social with the value of (0.485) and (0.469) have an average level of sustainability and the environmental aspect with a value of (0.383) has a nearly unsustainable level. According to human well-being, among the 10 counties studied, only the city of (Sareyn), has an almost unsustainable level, eight cities (Khalkhal, Kosar, Garmi, Nir, Meshgin Shahr, Namin, Pars Abad, and Bableh Savar) have an average level of sustainability and a city of (Ardebil) has at an almost sustainable level. Also in terms of well-being of ecosystems of the counties studied, it suggests that seven cities (Garmi, Nir, Sareyn, Namin, Bableh Savar, Meshgin Shahr, and Khalkhal) are almost unsustainable, and three cities (Kosar, Pars Abad, and Ardabil) have an average level of sustainability. Extended Abstract 1-Introduction With the beginning of the industrial revolution in Europe and spreading it around the world, significant changes was made in human life. Increased food production and improved health, led to the increased population of the world. In accordance to this increase, it is anticipated that the population of the world increases to nine billion, from the existing six billion (United Nations, 2008). The increased population along with the development of industrial society, pollution and destruction of the environment, are turned into new problems and they have alarmed a danger in the world. It was here when the focus on development, was considered rather than the growth (Sarai & Alizadeh Shoorki, 2015: 452; Newton, 2012: 81; Baker, 2006: 18). Major development approaches in the twentieth century to respond to crises and problems caused by the above events included the approaches of modernization, dependence, neo-liberal economics, alternative development etc., which were all ineffective, hence the sustainable development approach was publically accepted as the subject of the day of the last decade of the twentieth century, in the late 1980s, after being raised in Our Common Future conference known as the Brundtland report. The result of this conference was a global agenda for a change in the concept and the practice of development (Cowen & Shenton. 2005. 2; Withford, 2009: 6; Barton et al. 2003: 18; Roseland, 1997: 199). Sustainability, as one of the important concepts of planning, is emerged in economics and environmental thought since its beginning, and then widely used to evaluate development (Hiremath et al. 2013: 555). 2-Materials and Methods The research method is descriptive-analytical and quantitative. The population consists of 10 counties of Ardebil Province, based on census in 2015 and 2014. 3 economic, social and environmental components consisting of 10 economic indices, 16 social indices, and 14 environmental indices were used to evaluate. In this study, Analytic Network Process model (ANP) was used to express the relative importance of each indicator, and the sustainable barometer model was used to analyze the data. Besides, three economic, social, and environmental components including 10 economic indices, 16 social indices, and 14 environmental indices are used for assessment. Based on the results of the literature and source of the following indicators were used as indicators of evaluation and research. 3-Results and Discussion According to the results of sustainability barometer of 10 counties studied, 7 counties including Garmi (0.264), Nir (0.276), Sareyn (0.289), Namin (0.318), Bilesuar (0.381), Khalkhal (0.382), and Meshgin Shahr (0.395), respectively have an almost unsustainable status, and the counties of Kosar (0.438), Pars Abad (0.499), and Ardebil (0.586) have an average sustainability status. Radar movement towards environmental sustainability of Ardabil Province presents the movement of the top of the chart to the county of Ardabil. Ardabil as the capital of the province has the best environmental performance compared to the rest of the counties. Indices like the population under coverage drinking water network, urban green space, the number of wastewater branches and waste amount under management of hospitals with a score of (1.000) have the most positive effect on the sustainability of Ardabil, and the indices such as the area of natural forests (0.000) have the least positive impact on sustainability. Also, the reason of unsustainability of the city of Garmi, was that among the 14 economic indices assessed in this study, 8 indices had the least positive impact (0.000) in the sustainability of Garmi, and only the inverse index of percent of annual drainage of underground waters resources (1.000) had a complete positive impact. Moreover, the whole of Ardabil Province in terms of environmental sustainability, with a score of (0.383) is in a state of almost unsustainable. 4-Conclusions Rapid growth of cities’ populations in the developing countries due to the high rate birth and immigration from countryside to city, has increased the resource consumption and emission of pollution in them, and today, not only has it disrupted the economic and social balance within cities, but it has led to lack of regional ecologic balance within which they are located. Cities on the one hand, are considered as the centers of social, economic, and space development and on the other hand, they are the best places within which economic, environmental and social problems occur. In order to develop a scientific and rational basis for the policy maker to solve these shortcomings and sustainable spatial organization, the first step is to identify the effective factors on urban unsustainability and quantitative measurement and its spatial representation. Accordingly, the present study aimed at assessing and evaluating the sustainability of development in the counties of Ardabil Province in terms of the economic, social and environmental components. In this study, in order to express the relative importance of each index, the ANP model, and to analyze the data, the barometer sustainability model have been used. The results show that, based on economic sustainability, Sareyn County has a unsustainable status, counties of Pars Abad, Namin, Khalkhal, Meshgin Shahr, Garmi, Kosar, and Nir have an average sustainable status and the counties of Ardabil and Bilesuar are almost sustainable. According to social sustainability, county of Kosar, Nir and Bilesuar are almost in an unsustainable status and the counties of Garmi, Sareyn, Khalkhal, Meshgin Shahr, Namin, Ardebil, and Pars Abad are in an average sustainable status. Based on the environmental sustainability, the counties of Garmi, Nir, Sareyn, Namin, Bilesuar, Khalkhal, and Meshgin Shahr are in an almost unsustainable status and counties of Kosar, Pars Abad, and Ardabil are in an average sustainable status.